2003
DOI: 10.1097/01.phm.0000083671.27501.47
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dalteparin and Enoxaparin for Deep Venous Thrombosis Prophylaxis in Patients with Spinal Cord Injury

Abstract: Similar compliance, health status, deep venous thrombosis, and bleeding rates were found between dalteparin and enoxaparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 16 publications
0
30
0
2
Order By: Relevance
“…Nineteen other trials enrolled diverse groups of moderately to severely injured patients, including eight trials in patients with spinal cord injury 30,[166][167][168][169][170][171][172] and four studies in patients with orthopedic injuries. [173][174][175][176] Studies evaluated both mechanical (eg, IPC, myostimulation, continuous passive motion) and pharmacologic (eg, LDUH, LMWH) interventions, but no randomized trials examined IVC fi lter placement or use of surveillance ultrasound.…”
Section: Explanation Of Evidence Profi Lesmentioning
confidence: 99%
“…Nineteen other trials enrolled diverse groups of moderately to severely injured patients, including eight trials in patients with spinal cord injury 30,[166][167][168][169][170][171][172] and four studies in patients with orthopedic injuries. [173][174][175][176] Studies evaluated both mechanical (eg, IPC, myostimulation, continuous passive motion) and pharmacologic (eg, LDUH, LMWH) interventions, but no randomized trials examined IVC fi lter placement or use of surveillance ultrasound.…”
Section: Explanation Of Evidence Profi Lesmentioning
confidence: 99%
“…The definitive reason for this cannot be offered, especially because an extended literature search has shown multiple studies and metanalyses comparing UFH with LMWH, but head to head comparisons of the different LMW heparins are few in number and these have claimed similar compliance, health status, deep venous thrombosis, and bleeding rates with both [11] while some studies have brought out that switching patients from enoxaparin to dalteparin was cost-effective [12]. However the DETECT trial has established the hypothesis that dalteparin 5,000 units subcutaneous (SC) daily may not be clinically non-inferior to enoxaparin 30 mg SC twice daily for venous thromboembolism prophylaxis in high-risk population and until an adequately powered, prospective noninferiority trial is performed, enoxaparin is supported by level 1 evidence and should be the prophylactic agent of choice [13].…”
Section: Discussionmentioning
confidence: 99%
“…In acute SCI, a small randomized trial comparing enoxaparin to dalteparin reported similar protection and bleeding between the two preparations (Chiou-Tan, 2003). There appears to be no difference in the effectiveness of prevention of VTE following SCI between the commercially available LMWH preparations.…”
Section: Rationale For Thromboprophylaxismentioning
confidence: 99%